2020
DOI: 10.1177/1440783320960530
|View full text |Cite
|
Sign up to set email alerts
|

A woman’s place is in the ‘home’? Gender-specific hiring patterns in academia in gender-equal Norway

Abstract: We investigated women’s hiring patterns in academia, bridging the gap between two streams of literature typically not brought in conversation with one another: (1) access to tenured professorship by gender; (2) academic mobility and the disadvantage it can create for women. We studied all recruitments of new permanent associate and full professors by open call from 2007 to 2017 at one faculty of the largest university in Norway (N = 1009 applicants). We found that women were not reluctant to apply, nor systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 115 publications
(122 reference statements)
0
14
0
Order By: Relevance
“…They are older and more permanent than any political ideology (such as NPM) that is used to justify exclusion in specific historical phases. While NPM certainly does not serve the cause of women, historical gender marginalization in academia is insufficiently accounted for in NPM-focused critiques; this holds for exclusion both in terms of sheer numbers (Moratti 2020a;2020b), and of exclusionary representations (such as stereotypes of women's abilities) (Moratti 2018;. Managerialism in academia is a natural enemy of diversity, but there are others, older, more normalized and hence better concealed.…”
Section: Discussionmentioning
confidence: 99%
“…They are older and more permanent than any political ideology (such as NPM) that is used to justify exclusion in specific historical phases. While NPM certainly does not serve the cause of women, historical gender marginalization in academia is insufficiently accounted for in NPM-focused critiques; this holds for exclusion both in terms of sheer numbers (Moratti 2020a;2020b), and of exclusionary representations (such as stereotypes of women's abilities) (Moratti 2018;. Managerialism in academia is a natural enemy of diversity, but there are others, older, more normalized and hence better concealed.…”
Section: Discussionmentioning
confidence: 99%
“…What follows is a brief account of how the idea for this research came about, and the methods I have used. I started to discern a 'myth and tale' semantic pattern by serendipity, while researching metaphors on women academics (Moratti, 2018) and by reading scholarly material for a set of empirical studies on gender and tenure (Moratti, 2020a(Moratti, , 2020b. As my intuition gradually took shape, I further investigated the matter through internetmediated qualitative content analysis (Hewson et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…I found that women (and only women) are advantaged when already working at the institution (internal applicants) and disadvantaged when external applicants. Women apply as external applicants nearly as much as men do, but tend not to be preferred (Moratti, 2020b). This is especially true for women applicants affiliated with a non-Norwegian institution.…”
Section: Normativitymentioning
confidence: 95%
“…factors beyond individuals' direct agency) has examined the effects of institutional policies and practices on women's careers and explored the broader effects of academic and disciplinary cultures (Fagan and Teasdale, 2020;Berheide and Walzer, 2014;Howe-Walsh and Turnbull, 2016). These findings showed that academia is a conservative environment where women struggle to find legitimacy, even when gender equality is supported (O'Connor, 2020;Bönisch-Brednich and White, 2021;Moratti, 2021;Cohen et al, 2021). Often, neither an increase in the proportion of women (Helitzer et al, 2017) nor the presence of gender equality initiatives (Tzanakou and Pearce, 2019;Roos et al, 2020) is enough to change these deeply-ingrained power dynamics.…”
Section: Balance Between Status Quo and Changementioning
confidence: 99%